Quadrivalvular nonbacterial thrombotic endocarditis in a patient with clear cell cervical cancer - Gabelmann, Valentin; Grabs, Felix; Diestelmeier, Simon; Heindl, Felix; Vosseler, Markus; Muenzel, Thomas; Sagoschen, Ingo; Wild, Johannes (Clinical Case Reports, 2022)
Nonbacterial thrombotic endocarditis (NBTE) is a rare finding, which is mostly associated with malignant diseases leading to hypercoagulability. We report the case of a severe quadruple valve nonbacterial thrombotic endocarditis in a patient with clear cell cervical cancer.
CRIS-Team WoS Importer:2022-10-28